2012
DOI: 10.2519/jospt.2012.4077
|View full text |Cite
|
Sign up to set email alerts
|

Return to Preinjury Sports Participation Following Anterior Cruciate Ligament Reconstruction: Contributions of Demographic, Knee Impairment, and Self-report Measures

Abstract: STUDY DESIGN Cross-sectional cohort. OBJECTIVES (1) To examine differences in clinical variables (demographics, knee impairments, and self-report measures) between those who return to preinjury level of sports participation and those who do not at 1 year following anterior cruciate ligament reconstruction, (2) to determine the factors most strongly associated with return-to-sport status in a multivariate model, and (3) to explore the discriminatory value of clinical variables associated with return to sport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
193
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(215 citation statements)
references
References 60 publications
17
193
0
Order By: Relevance
“…23 Similarly, when using the IKDC, studies have shown that higher proportions of athletes have returned to sport following ACL reconstruction when their IKDC scores were greater than 90. 36 Therefore, the criterion cutoff used in this study for the IKDC was a score of 90 or greater.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…23 Similarly, when using the IKDC, studies have shown that higher proportions of athletes have returned to sport following ACL reconstruction when their IKDC scores were greater than 90. 36 Therefore, the criterion cutoff used in this study for the IKDC was a score of 90 or greater.…”
Section: Resultsmentioning
confidence: 99%
“…15 Importantly, previous work has found that individuals who returned to their preinjury level of sports participation after ACL reconstruction had a higher IKDC score (93.8 ± 6.3) than those who did not return to their preinjury level of sports participation (78.0 ± 15.6). 36 While previous studies have reported proportions of individuals after ACL reconstruction who meet cutoffs for various measures, 23,57 the number of young athletes meeting recommended criterion cutoffs at the specific time of return-tosport clearance and the impact of meeting criterion cutoffs on longitudinal sports participation remain unreported. This is particularly important, given suboptimal return-to-sport outcomes over time following ACL reconstruction.…”
Section: U U Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probably, ACL not only prevents tibial displacement to anterior position to avoid instability in other directions such as valgus and varus but also play a major role in individual sense of stability toward the knee. [9] Therefore, relying on anterior drawer and Lachman test results as [10] Since Lysholm score generally and comprehensively evaluates several indicators such as pain, locking the knee, and swelling, these scores are used as the most important indices in evaluating surgical results and the patients' satisfaction. Relying on the knee instability tests alone cannot ensure the success of the treatment and knee function.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic, physical and psychological factors have shown to affect RTS rate following ACL reconstruction (5). Previous studies suggested that only detecting side to side asymmetries by using physical performance tests is not adequate for RTS decision (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%